(untitled) (Comparative Professional Pedagogy, 2023)
The article examines the specifics of teacher training for specialized foreign language teaching in Ukraine and foreign countries. It is established that in the context of globalization and integration processes and the introduction of the New Ukrainian School concept into the educational system, the needs related to foreign language teaching have changed. This applies to specialized schools particularly, because the transition to specialized training is one of the vital components for the implementation of the new requirements. Thus, the content of education is focused on the implementation of competence and personal approaches in education, and a foreign language teacher is expected to fulfill new roles as a mediator, facilitator and mentor. It is found that in the case of Great Britain, future foreign language teachers can obtain qualifications both in institutions of higher education and by means of specialized courses or postgraduate education in the field of pedagogy. The specifics of professional training of future foreign language teachers in other countries are studied. Tendencies and models of teacher training in El Paso are analyzed and the requirements for the activities of graduates of the pedagogical specialties of the University of Texas are determined. The skills and competencies that should be developed in the future teachers of Chilean universities are studied and grouped. Strategies for training foreign language teachers in Great Britain are analyzed. Specifics of the external form of education and factors of its effectiveness for the preparation of teachers to work in a specialized school are studied. The process of preparation for specialized training of Ukrainian teachers of foreign languages is analyzed. The principles that underlie the preparation of teachers for work in specialized schools are outlined. Prospects of creating a special program for professional training of future teachers are studied. As a result of the analysis, it is determined that a complex approach with a combination of traditional and modern forms and methods of teaching prevails in the preparation of future teachers for specialized teaching abroad. Ukrainian tendencies were compared to the foreign ones and it is found that modern domestic scientists are inclined to the foreign ideas. However, the training strategy needs further research and implementation of more ideas from positive foreign experience.